Measurement of the production and lepton charge asymmetry of W bosons in Pb+Pb collisions at √sNN = 2.76 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
A measurement of W boson production in lead-lead collisions at √sNN = 2.76 TeV is presented. It is based on the analysis of data collected with the ATLAS detector at the LHC in 2011 corresponding to an integrated luminosity of 0.14 nb-1 and 0.15 nb-1 in the muon and electron decay channels, respectively. The differential production yields and lepton charge asymmetry are each measured as a function of the average number of participating nucleons ‹Npart› and absolute pseudorapidity of the charged lepton. The results are compared to predictions based on next-to-leading-order QCD calculations. These measurements are, in principle, sensitive to possible nuclear modifications to the parton distribution functions and also provide information on scaling of W boson production in multi-nucleon systems.